Captain Phillips - Greengrass, Paul; Hanks, Tom; Abdi, Barkhad; Keener, Chaterine (Culver City, California : Columbia Pictures Industries, Inc., 2013)
Captain Phillips is a multi-layered examination of the 2009 hijacking of the U.S. container ship Maersk Alabama by a crew of Somali pirates. Based on a true story, the film focuses on the Alabama's commanding officer, Captain Richard Phillips and the Somali pirate captain, Muse, who takes his hostage. The two man are set on an unstoppable collision course when Muse and his crew target Phillips' unarmed ship; in the ensuing standoff, both men will find themselves at the mercy of forces beyonf their control.
Based upon the book'A Captain's duty: Somali pirates, Navy Seals, and dangerous days at sea' by Richard Phillips with Stephan Talty.
Director of photography, Barry Ackroyd ; editor, Christopher Rouse ; music, Henry Jackman.
Tom Hanks, Barkhad Abdi, Chaterine Keener.
Filmed on location in Malta, United Kingdom, Virginia, Massachusetts and Morocco.
LPF: P13.
DVD format, Region 3, Dolby Digital.
Keywords: Phillips, Richard, -- 1956- -- Drama; Maersk Alabama (Ship), -- Drama; Hijacking of ships -- Somalia -- Drama; Action and adventure films